2018
DOI: 10.1002/pc.24743
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of flexible/stretchable polyimide having long/bulky aryl pendent group and polyimide/silicon dioxide nanocomposites.

Abstract: A new diamine monomer having ether and azomethine linkages in the long pendent group was synthesized. New polyimide was prepared by reacting the new diamine with BTDA and nanocomposites were prepared with silicon dioxide as nanofiller. SEM analysis shows a uniform distribution of the nanopowder in the polyimide matrix. TGA shows that the polyimide and nanocomposites have good thermal stability with the T10% values varying between 440 and 458°C. DSC analysis shows Tg values between 210 and 230°C. The neat polyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Here, the elongation is less compared to that in our previously published work in which one long aromatic pendent group is present. 27 In 2007 Wang et al 8 reported that poly etherimides with multiple alkyl side chains (number of CH 2 groups in each chain varies from 5 to 18) showed very high elongation at break (200–470%). Tensile strength of those polyimides was found to be low.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the elongation is less compared to that in our previously published work in which one long aromatic pendent group is present. 27 In 2007 Wang et al 8 reported that poly etherimides with multiple alkyl side chains (number of CH 2 groups in each chain varies from 5 to 18) showed very high elongation at break (200–470%). Tensile strength of those polyimides was found to be low.…”
Section: Resultsmentioning
confidence: 99%
“…In one of our recently published work, the polyimide having single pendent groups exhibits high elongation at break of 260%. 27 The effect of side groups in the polyimide chain backbone on thermal, mechanical and electrical properties were investigated in detail by Meise et al 28 and Deng et al 29 …”
Section: Introductionmentioning
confidence: 99%